Analisis Indeks Kesesuaian Garam (IKG) Untuk Menentukan Kesesuaian Lokasi Produksi Garam di Provinsi Aceh - Hamdani; Farmiati, Josi (Journal of Law and Economics, 2022)
Salt for the people of Aceh is a very important commodity. Salt is not only used for household consumption, it is even used by industry as an additional raw material for production so that the level of demand for salt is now increasing as a result of a deficit in supply due to a shortage of stock. This situation has forced the government to import salt to meet domestic needs. One of the factors that determine the success of salt production is the land and location that is suitable. This study aims to obtain the Salt Suitability Index (IKG) which is used as a reference for analyzing the suitability of salt production locations so that there are no wrong targets in decision making. This research was conducted with a field survey in collecting primary data with a research period from March to December 2019. The method used in this research is a descriptive method with Conformity Index analysis. The results showed that eight districts in Aceh consisted of Aceh Besar, Pidie, Pidie Jaya, Bireuen, North Aceh, East Aceh, Abdya and South Aceh districts which were used as the leading areas for salt production in accordance with the total IKG value of each location> 85% or category (S1). This study reports the first IKG analysis of salt production locations and fields in Aceh that may be of use to policy makers and further study by other researchers.